Mode of action of elasnin as biofilm formation eradicator of methicillin-resistant Staphylococcus aureus - Long, Lexin; Sulaiman, Jordy Evan; Xiao, Yao; Cheng, Aifang; Wang, Ruojun; Malit, Jessie James; Wong, Wai Chuen; Liu, Wenchao; Li, Yong-Xin; Chen, Feng; Lam, Henry; Qian, Pei-Yuan (Frontiers in Microbiology, 2022)
Biofilm is made up of microbes and their extracellular matrix, making microorganisms highly tolerant, resistant, and resilient to a wide range of antimicrobials. Biofilm treatment with conventional antimicrobial agents can accelerate the evolution and spread of resistance due to the reduced efficacy and increased gene transfer and differentiation within biofilms. Therefore, effective biofilm-targeting compounds are currently highly sought after. In the present study, we identified elasnin as a potent biofilm-targeting compound against methicillin-resistant Staphylococcus aureus (MRSA). Elasnin effectively inhibited biofilm formation and especially eradicated the pre-formed biofilms of MRSA with low cytotoxicity and low risk of resistance development and retains its activity in a chronic wound biofilms model. A comprehensive mechanistic study using multi-omics and confocal and scanning electron microscopy revealed that elasnin induced the biofilm matrix destruction in a time-dependent manner and interfered with the cell division during the exponential phase, primarily by repressing the expression of virulence factors. Cells released from the elasnin-treated biofilms exhibited a defective appearance and became more sensitive to beta-lactam antibiotic penicillin G. Through gene overexpression and deletion assay, we discovered the key role of sarZ during elasnin-induced biofilm eradication. Overall, the present study identified elasnin as a potent biofilm eradicator against MRSA that harbors potential to be developed for biofilm removal and chronic wound treatment, and provided new insights into the molecular targets for biofilm eradication in MRSA.